2016
DOI: 10.1111/cbdd.12758
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation of Uridine with Oleanolic Acid Derivatives as Potential Antitumor Agents

Abstract: According to fused two bioactive moieties together by bonds covalently and available as a new single hybrid entity known as pharmacophore hybridization, a total of 10 targeted uridine-oleanolic acid hybrids were synthesized. Most of these hybrids showed excellent proliferation inhibition against tested Hep-G2, A549, BGC-823, MCF-7, and PC-3 tumor cell lines (IC50 < 8 μm), even with some IC50 values under 0.1 μm. The detection of cytotoxicity selectivity revealed that hybrids 5 and 18 exhibited low cytotoxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…In recent years, uridine, uracil, and thymine (2, 3, and 4, Figure 1) have attracted much interest due to their promising potential biological activities, and their modified derivatives have exhibited excellent activities, such as antibacterial, inhibition against 1,4-β-galactosyltransferase, antivirus, anticancer, and so on [29][30][31][32][33][34][35][36]. Our previous studies [37,38] have also shown that uridine/uracil/thymine attached to the natural compound oleanolic acid could afford derivatives that possess high anti-proliferative activities against tumor cell lines and exhibit clearly inducing effects on cell apoptosis.…”
Section: -Methoxyestradiolmentioning
confidence: 99%
“…In recent years, uridine, uracil, and thymine (2, 3, and 4, Figure 1) have attracted much interest due to their promising potential biological activities, and their modified derivatives have exhibited excellent activities, such as antibacterial, inhibition against 1,4-β-galactosyltransferase, antivirus, anticancer, and so on [29][30][31][32][33][34][35][36]. Our previous studies [37,38] have also shown that uridine/uracil/thymine attached to the natural compound oleanolic acid could afford derivatives that possess high anti-proliferative activities against tumor cell lines and exhibit clearly inducing effects on cell apoptosis.…”
Section: -Methoxyestradiolmentioning
confidence: 99%
“…in the presence of potassium carbonate (1 equiv.) to prepare compounds 4a/4b-6a/6b 28,31 in moderate to good yield (62-89%). Compounds 4a/4b-6a/6b (1 equiv.)…”
Section: Synthesismentioning
confidence: 99%
“…27 Based on pharmacophore hybridization, our group has already reported several series of pentacyclic triterpene conjugates and some of them possess much better inhibition of proliferation as well as the cytotoxicity selectivity as compared to monomer pentacyclic triterpenes and the commercial anticancer drug 5-FU. 28,29 For example, the dimeric oleanolic acid linked at C-28 by 1,6-hexanediamine displayed moderate cytotoxicity towards Hep-G2, A549, BGC-823, MCF-7 and PC-3 tumor cell lines with the IC 50 value under 10.0 μM, while low cytotoxicity against the normal human liver cell HL-7702. 30 Inspired by the evidence, in this study, 5-FU was respectively attached to the natural products OA/UA/ GA to afford conjugates of pentacyclic triterpene-5fluorouracil (Schemes 1 and 2, 7a/7b-12a/12b) and their antitumor activities were evaluated (Table 1).…”
mentioning
confidence: 99%
“…Furthermore, uridine has been increasingly used as precursors for antivirus and antitumor drugs in pharmaceutical industry [2, 3]. Chemical synthesis is the commercial method for uridine production by the condensation reaction of uracil and D-ribose, however, the expensive raw materials increase the production cost.…”
Section: Introductionmentioning
confidence: 99%
“…Uridine and its nucleotide derivatives play an important role in the biochemical and physiological processes including the synthesis of DNA, RNA, membrane constituents and glycosylation [ 1 ]. Furthermore, uridine has been increasingly used as precursors for antivirus and antitumor drugs in pharmaceutical industry [ 2 , 3 ]. Chemical synthesis is the commercial method for uridine production by the condensation reaction of uracil and D-ribose, however, the expensive raw materials increase the production cost.…”
Section: Introductionmentioning
confidence: 99%